2021
DOI: 10.1186/s12883-021-02143-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients admitted to hospitals for posterior reversible encephalopathy syndrome: a retrospective cohort study

Abstract: Background Posterior reversible encephalopathy syndrome (PRES) is usually a benign, yet underdiagnosed clinical condition associated with subacute to acute neurological manifestations primarily affecting white matter. PRES is reversible when recognized promptly and treated early by removal of the insulting factor; however, can lead to irreversible and life-threatening complications such as cerebral hemorrhage, cerebellar herniation, and refractory status epilepticus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…A previous study of patients hospitalized with PRES showed that PRES mostly affected women (71.7%), 87.0% of patients had hypertension and 45.5% had hypertensive crisis. 11 In another study, patients with PRES mostly presented with seizures (74.0%), encephalopathy (28.0%), headache (26.0%) and visual disturbances (20.0%), and 45.0% of patients had autoimmune diseases, including thrombotic thrombocytopenic purpura and SLE. 9 Our patient had SLE and hypertension as risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study of patients hospitalized with PRES showed that PRES mostly affected women (71.7%), 87.0% of patients had hypertension and 45.5% had hypertensive crisis. 11 In another study, patients with PRES mostly presented with seizures (74.0%), encephalopathy (28.0%), headache (26.0%) and visual disturbances (20.0%), and 45.0% of patients had autoimmune diseases, including thrombotic thrombocytopenic purpura and SLE. 9 Our patient had SLE and hypertension as risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…Despite PRES being a well-known entity, it remains underdiagnosed given its variable clinical presentations. 2 For our patient, non-organic cause of vision loss was entertained and assessed with optokinetic testing given the initial vague combination of visual changes, hypertension, and renal abnormality (though our patient did eventually develop seizure after diagnosis of PRES). Nevertheless, since as high as 9.9% of patients have vision loss in PRES, 2 it is important for ophthalmologists to obtain detailed history, attend to vital signs, and consider pathology in the retro-orbital visual pathway when there is no evidence of ocular abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, visual changes is a poor diagnostic criterion for PRES and a high clinical suspicion is needed. 2 , 3 Certainly, while PRES can be reversible, it is not always the case and can in fact lead to death in 3–6% of cases secondary to intracranial hemorrhage, increased intracranial pressure, and hydrocephalus or brain stem compression from cerebral edema. 1 As a result, PRES requires prompt workup and timely management of the underlying condition.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies have reported varying PRES-associated mortality ranging from 2.2% to 26.9%. [12][13][14][15] However, most of these studies are limited by small sample sizes or focused on intensive care unit patients who may be sicker than the average patient. 14 Remarkably, whereas outcome after PRES is expected to be favorable, we found that <50% of patients with PRES are discharged home without assistance.…”
Section: Discussionmentioning
confidence: 99%